Estratégias políticas da lusofonia ou a Comunidade dos Países de Língua Portuguesa (África, 1998)
The paper draws the attention to the strategic importance of the cultural identity, based on language, to the reconstruction of the concept of nation and frontiers in contemporary world. Due to the process of internationalization of national economies, communities would be recognized lesser by political institutions and more by cultural aspects. So, the use and speech of the Portuguese language would be and new element of insertion in other regional spaces, by creating a worldwide cultural system on continuity. Action in this sense is urgent.